NONLINEAR CONTROL ON THE BOUNDARY OF CUBIC CRYSTALS - Santiago Ayala, Yolanda Silvia (2010)
sing monotone maximal operators Theory and the Minty-Browder theorem, we prove the existence of global solution to the elastic-dynamic system on cubic crystals, which is given a nonlinear control f. Also, using multiplicative techniques, results of R. Dautry. - J. L. Lions, integral inequalities, Russel' Principie, the W. Liu method, and adapting the F. Conrad and B. Rao method in the calculation of the estimates, we show that the energy associated to the system decays to zero when t → +∞.